As atitudes do consumidor em relação à propaganda - Perrupato, Luís Carlos (2006)
The research approaches the issue of attitudes, more specifically, the beliefs and feelings of the consumer, with regard to the advertisement. For that, it was sought know the advertisement concepts, of attitudes, its components that were nearer to the objective of the research. The attitudes toward the advertisement that were more present in the literature researched were: incredulity, credibility, damage, positive and negative feelings; feelings of pleasure, enrapturing (warm), and skepticism. It was also identified that the materialistic attitude is a strong influence indicator for consumerism. Moreover, the misleading advertising showed itself harmful to the individuals in general, and particularly to the children, who are more susceptible. The methodology applied was the exploratory research, through bibliographical survey.